Practical considerations for nonfactor‐replacement therapies in the treatment of haemophilia with inhibitors. Issue 3 (20th March 2021) - Jiménez‐Yuste, Victor; Auerswald, Günter; Benson, Gary; Dolan, Gerry; Hermans, Cedric; Lambert, Thierry; Ljung, Rolf; Morfini, Massimo; Santagostino, Elena; Zupančić Šalek, Silva
Abstract: New therapeutic agents for haemophilia with inhibitors that are in development or already licensed are expected to provide transformative treatment options. Many of these new therapies are not based on simply replacing the missing factor; new strategies include bispecific antibody technology that mimics factor VIII coagulation function (emicizumab), and inhibition of anticoagulant proteins such as tissue factor pathway inhibitor (eg PF‐06741086) and antithrombin (eg fitusiran). These agents are administered subcutaneously and should significantly reduce treatment burden and increase the ability to deliver prophylaxis for patients. Limited real‐world data and validated practical guidance on these recently licensed/upcoming treatments resulted in the authors convening to discuss recommendations on their use. Emicizumab is currently the only licenced nonfactor therapy; thus, our recommendations focus on this product. Target candidates for emicizumab prophylaxis are difficult‐to‐treat patients with haemophilia A and inhibitors and/or venous access issues, frequent bleeds and target joints. In case of breakthrough bleeding while receiving emicizumab, patients still require treatment with bypassing agents; the adjunct treatment of choice is recombinant activated factor VII. This treatment is also recommended to prevent bleeds in patients with inhibitors undergoing surgery. Our recommendations on suitable laboratory assays and monitoring new products, as well as the benefit of patient‐reported outcomes (such as pain and physical activity levels), are included. We also briefly discuss future treatment options for patients with haemophilia B and inhibitors. Although these nonfactor treatments offer great promise, further data and real‐world evidence are needed.